Smart Refrigerator Mobile Application - Mohd Shuzardi, Muhammad Amirul Afiq (IRC, 2019)
Smart Refrigerator Mobile Application is an android-based application to be used on a smartphone and android tablet. The problem discovered behind development of this application to be cause by the difficulties in determining and unawareness of consumer about the expiration date on their food items. In conjunction with the problem discovered, the objective of this project is to notify consumer food items that will soon expired. The other objective is to developed Android-based mobile application, named Smart Refrigerator that incorporated all the element that have been identified and evaluate the user acceptance. Development of Smart Refrigerator is to spread awareness to consumer and to minimize food wastage in Malaysia. For this purpose, Smart Refrigerator mobile application will act as information center for consumer that will remind user a few days to ensure user have the information about food items that will be unable to consume soon. Android-based system (OS) is chosen as the platform for this application because Android proved to be efficient, user friendly and OS are used widely on most of smartphone developer. In term of methodology, Rapid Application Development (RAD) will be practiced as author have time constraint due to only 28 weeks to development Smart Refrigerator mobile application. User acceptance will be conducted to Seri Iskandar, Perak residence that owned fridge.